The Role of Tourism Activities in Alleviating the Management Cost of Puri Agung Kerambitan, Tabanan - Lirishati Soethama, Putu; Istri Aryani, I Gusti Agung (Udayana Journal of Social Sciences and Humanities; Vol 2 No 2 (2018): UJoSSH, September 2018DO - 10.24843/UJoSSH.2018.v02.i02.p08, 2018)
Puri Agung Kerambitan is the forerunner of pekraman village Kerambitan, Tabanan, Bali. Its vast territory covers 19 villages from Kerambitan in the south to Batuaji in the north of the palace. It is founded in 1650 as a fragment of the Kingdom of Tabanan, began to open its access to tourism in 1980, during the reign of Late A A. Ngurah Anom Mayun. Puri Agung offers several activities such as Puri Wedding, Puri Day and Puri Night Dinner for more than three decades. All of these activities involve the palace residents and villagers surrounding it. Arts attraction such as Tabuh Okokan and Tektekan Calonarang, distinctive and authentic of Kerambitan art; until the procedure of making offerings and traditional Balinese cake are displayed. The number of foreign and domestic tourists who visit the palace is certainly has a big impact on the grand cost of the palace management cost. The income and the expenses of the palace within 2016 was obtained by using a quantitative method. Interviews with the management and residents of Puri Agung Kerambitan were conducted for the validity and supporting the research data. The data and problem were analyzed using the qualitative descriptive method. This paper gives an overview and simple description of Puri Agung Kerambitan's income from its tourism activity and the expenses required for managing it. These expenses can be sorted out in physical, such as palace maintenance and staff salaries; as well as non-physical, such as ceremonial financing. The good management of tourism activities could alleviate the grand maintenance cost of the palace.